Practical Linux security cookbook : secure your Linux machines and keep them secured with the help of exciting recipes - Kalsi, Tajinder (Quick answers to common problems., 2016)
Secure your Linux machines and keep them secured with the help of exciting recipes About This Book This book provides code-intensive discussions with detailed recipes that help you understand better and learn faster. More than 50 hands-on recipes to create and administer a secure Linux system locally as well as on a network Enhance file system security and local and remote user authentication by using various security tools and different versions of Linux for different tasks Who This Book Is For Practical Linux Security Cookbook is intended for all those Linux users who already have knowledge of Linux File systems and administration. You should be familiar with basic Linux commands. Understanding Information security and its risks to a Linux system is also helpful in understanding the recipes more easily. However, even if you are unfamiliar with Information security, you will be able to easily follow and understand the recipes discussed. Since Linux Security Cookbook follows a practical approach, following the steps is very easy. What You Will Learn Learn about various vulnerabilities and exploits in relation to Linux systems Configure and build a secure kernel and test it Learn about file permissions and security and how to securely modify files Explore various ways to authenticate local users while monitoring their activities. Authenticate users remotely and securely copy files on remote systems Review various network security methods including firewalls using iptables and TCP Wrapper Explore various security tools including Port Sentry, Squid Proxy, Shorewall, and many more Understand Bash vulnerability/security and patch management In Detail With the growing popularity of Linux, more and more administrators have started moving to the system to create networks or servers for any task. This also makes Linux the first choice for any attacker now. Due to the lack of information about security-related attacks, administrators now face issues in dealing with these attackers as quickly as possible. Learning about the different types of Linux security will help create a more secure Linux system. Whether you are new to Linux administration or experienced, this book will provide you with the skills to make systems more secure. With lots of step-by-step recipes, the book starts by introducing you to various threats to Linux systems. You then get to walk through customizing the Linux kernel and securing local files. Next you will move on to manage user...